Characteristics of Adult Students' Writing - Meyers, Miriam ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
Responding to students' needs for systematic advice about their writing, a city university developed a voluntary test using student writing samples to evaluate punctuation and grammar, diction, sentence structure, and organization and development. Evaluation of 100 test results revealed that these students, all working adults, showed more control over mechanics than over organization and development. Although all but 10 of the students had had previous college writing instruction, only 23% of the sample received a satisfactory score. After receiving their diagnostic test results, one-quarter of those eventually receiving degree candidacy registered for a nonrequired first-level writing course. These findings suggest the following: (1) a self-instruction format for teaching editing skills could free needed class time for work on more difficult problems with idea organization and development; (2) if given information about their writing problems, adult students will voluntarily register for additional instruction; and (3) instruction alone is not enough to improve writing skills--teachers in all subjects need to stress writing's value as an aid to both communicating and learning. (Test results and a profile of the tested population are appended.) (MM)
ERIC Note: Paper presented at the Annual Meeting of the Minnesota Council of Teachers of English (24th, Minneapolis, MN, May 6-7, 1983).
Educational level discussed: Higher Education.
Teachers.
Administrators.
Practitioners.
May also be available online. Address as at 14/8/18
Keywords: Adult Students; Diagnostic Teaching; Diagnostic Tests; Educational Diagnosis; Higher Education; Writing (Composition); Writing Evaluation; Writing Instruction; Writing Research; Writing Skills; Speeches/Meeting Papers; Reports, Research